Green Biochar based Catalysts for the Cleaning of Syngas Produced from Solid-Fuels Gasification - Witham, Matthew Ian (Curtin University, 2017)
Through the use of a moving bed of biochar-based catalyst, the tar concentration in a syngas produced from gasification of biomass can be reduced below 100 mg/m3. The spent catalyst, i.e. partially-gasified biochar, has desired nutrients leaching rate and water holding capacity so that it can be returned to soil for enhanced the agronomical benefits.